2014
DOI: 10.1161/circulationaha.113.002529
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Plasma Triglycerides and High-Density Lipoprotein Cholesterol and Microvascular Kidney Disease and Retinopathy in Type 2 Diabetes Mellitus

Abstract: Background-Microvascular renal and retinal diseases are common major complications of type 2 diabetes mellitus. The relation between plasma lipids and microvascular disease is not well established. Methods and Results-The case subjects were 2535 patients with type 2 diabetes mellitus with an average duration of 14 years, 1891 of whom had kidney disease and 1218 with retinopathy. The case subjects were matched for diabetes mellitus duration, age, sex, and low-density lipoprotein cholesterol to 3683 control subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
149
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(167 citation statements)
references
References 49 publications
12
149
1
5
Order By: Relevance
“…Likewise, in a large-scale study of 2535 patients with type 2 DM, retinopathy was not significantly associated with triglyceride or high-density lipoprotein (HDL) cholesterol levels after adjustment of confounding factors. 45 In contrast, Cheng at al 4 found that in overweight type 2 DM patients, elevated triacylglycerol levels were significantly associated with diabetic retinopathy (OR=1.29; 95% CI, 1.05-1.58; P<0.05).…”
Section: Hyperlipidaemiamentioning
confidence: 94%
“…Likewise, in a large-scale study of 2535 patients with type 2 DM, retinopathy was not significantly associated with triglyceride or high-density lipoprotein (HDL) cholesterol levels after adjustment of confounding factors. 45 In contrast, Cheng at al 4 found that in overweight type 2 DM patients, elevated triacylglycerol levels were significantly associated with diabetic retinopathy (OR=1.29; 95% CI, 1.05-1.58; P<0.05).…”
Section: Hyperlipidaemiamentioning
confidence: 94%
“…In the recent, very large META-EYE study, high total cholesterol level was a risk factor for diabetic retinopathy, specifically for diabetic macular edema [15]. In contrast, a 13-country study of long type 2 diabetes duration showed that plasma lipid levels (high triglycerides and low HDL-C levels) were associated with retinopathy on univariate analysis, but not at full adjustment for potential confounders [24]. In recent studies, we found that circulating levels of apolipoprotein A1 (associated with HDL) and apolipoprotein B (found in LDL, lipoprotein(a), VLDL, and chylomicrons) were stronger predictors of diabetic retinopathy than traditional lipid levels [182].…”
Section: Lipid-and Lipoprotein-related Biomarkersmentioning
confidence: 95%
“…A similar process can be observed for lipid levels. Whilst high total and LDL-cholesterol (LDL-C), triglycerides, and low HDL-C levels are traditional risk factors for cardiovascular disease, and possibly also for diabetic retinopathy [15,24], lipoprotein subclass profiles based on lipoprotein particle size [25], determined by nuclear magnetic resonance (NMR) and measures of circulating oxidized LDL [26], are more recently developed, and may thus be regarded as novel biomarkers.…”
Section: Types Of Biomarkersmentioning
confidence: 99%
“…Most recently, the evidence-base for a role for atherogenic dyslipidemia has been strengthened by the REALIST (REsiduAl risk Lipids and Standard Therapies) microvascular study [35]. This crosssectional case-control study included 2,535 type 2 diabetes patients with either diabetic kidney disease (n=1891), diabetic retinopathy (n=1,218) or both complications (n=574), and 3,683 matched controls, enrolled by 24 sites in 13 countries in Europe, North America, the Middle East, Asia (including Japan and China), and Australasia.…”
Section: A Role For Atherogenic Dyslipidemia?mentioning
confidence: 99%
“…In this context, management of atherogenic dyslipidemia, a key driver of cardiovascular risk in this patient group, in addition to best standards of care, is relevant as supported by evidence from the REALIST-Micro study [35]. In support, a large-scale study in a real-life setting suggested that improved lipid management, targeting HDL cholesterol and triglycerides in addition to non-HDL cholesterol, can reduce the risk of diabetic retinopathy, peripheral neuropathy, and/or nephropathy in type 2 diabetes patients [39].…”
Section: Conclusion R 3 I Recommendationsmentioning
confidence: 99%